A further modification of the elastic field of an edge dislocation - John P. Hirth; Jian Wang (Proceedings of the National Academy of Sciences, 2025)
A previous modification removed a nonphysical divergence of the elastic displacement field of an edge dislocation. The traditional elastic equations are correct to linear elastic order. However, there is a disregistry of the displacement field at ± infinity that significantly influences the elastic displacements and is missed in the linear elastic description. The earlier revision included volumetric nonlinear elasticity through the use of embedded coordinates and included the disregistry as well as removing the divergence. However, the revised model had a larger self-energy than the traditional model, which we now find to arise from similar divergent terms for the line force. The present model modifies the line force field to remove the divergent terms. The resultant total energy in the modified model has a lower energy than the traditional model.